(untitled) (Global Journal of Management and Business Research, 2018)
The recent economic and financial situations of Bangladesh have an impact on the banking system, raising a question about bank’s operational efficiency. Moreover, Bank’s operational efficiency is getting emphasized in the competitive financial market to satisfy both shareholders and depositor. The present study has assessed the impact of liquidity and profitability on the operational efficiency of scheduled commercial banks of Bangladesh over the period from 2011 to 2016. The study has used secondary data of 30 scheduled commercial banks of Bangladesh. The quantitative research has employed panel data approach using various models like Fixed Effect Regression model with Cluster-Standard Errors and Drisc/Kraay Standard Errors models, Feasible Generalized Least Square Model and Panel Correlated Standard Error Model to provide the robust result. The study reveals that liquidity and profitability combined explain about 66.23% and 98.85% of the bank’s operational efficiency under Fixed Effect Regression Model and Panel Correlated Standard Error estimator respectively. The study concludes that after maintaining minimum liquidity, the bank should utilize their customer’s deposits and borrowings through making high-quality loan portfolio to ensure earnings for their shareholders.